2017
DOI: 10.1007/s00442-017-3940-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism or behavior: explaining the performance of aphids on alkaloid-producing fungal endophytes in annual ryegrass (Lolium multiflorum)

Abstract: Plant-herbivore interactions are often mediated by plant microorganisms, and the "defensive mutualism" of epichloid fungal endophytes of grasses is an example. These endophytes synthesize bioactive alkaloids that generally have detrimental effects on the performance of insect herbivores, but the underlying mechanisms are not well understood. Our objective was to determine whether changes in the physiology and/or behavior of aphids explain the changes in performance of insects feeding on endophytic plants. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 82 publications
2
28
0
Order By: Relevance
“…<7 days) for both species, with very few nymphs reaching the adult stage on all endophyte treatments. The nymphal stage has been reported to be more susceptible to endophytes than the adult stage in other aphid species, such as R. padi [24]. This finding is of economic importance as early-acting insecticides that are most effective against nymphs will more successfully reduce aphid population growth, due to fewer aphids surviving to reproductive age.…”
Section: Insecticidal Activities Of Endophytes: Mortalitymentioning
confidence: 98%
See 2 more Smart Citations
“…<7 days) for both species, with very few nymphs reaching the adult stage on all endophyte treatments. The nymphal stage has been reported to be more susceptible to endophytes than the adult stage in other aphid species, such as R. padi [24]. This finding is of economic importance as early-acting insecticides that are most effective against nymphs will more successfully reduce aphid population growth, due to fewer aphids surviving to reproductive age.…”
Section: Insecticidal Activities Of Endophytes: Mortalitymentioning
confidence: 98%
“…Numerous studies have been carried out since the 1980s to determine what grass-endophyte association has the greatest negative effect on aphids but has minimal effect on vertebrates. In these studies, aphids' settling preferences, host acceptance, feeding, body size and life history parameters were assessed under a range of conditions [24][25][26][27][28]. A common trend across many studies has emerged that showed varying responses depending on the aphid-grassendophyte combination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Epichloë festucae symbiosis with ryegrass (Lolium perenne var. Lolii) enhances gene expression of jasmonic acid (JA) precursors [13], and the expression of the systemic defense genes HvPr17b and HvHsp70 in barley is associated with the presence of the endophyte Piriformospora indica [14]. Further, presence of endophytes may alter pathogenesis-related proteins (PR-proteins) concentration, as chitinase, peroxidase, glucanase and cellulase in cucumber inoculated with Trichoderma harzianum [15] The resistance induction is also related with the activity of defense enzymes, such as phenylalanine ammonia lyase, polyphenol oxidase, superoxide dismutase, peroxidase, ascorbate peroxidase, and guaiacol peroxidase.…”
Section: Biological Controlmentioning
confidence: 99%
“…The EPG technique has been widely used to investigate different aspects of insect-plant interactions. For example, EPG was used to characterize host plant resistance to hemipterans (Vanhelden & Tjallingii, 1993;Alvarez et al, 2013) to understand the transmission mechanisms of plant pathogens by their insect vectors (Fereres & Moreno, 2009;Moreno et al, 2012), to understand the mode of action of pesticides (Harrewijn & Kayser, 1997;Garzo et al, 2016), and to examine the feeding behavior of aphids on plants colonized by fungal endophytes (Bastias et al, 2017). Surprisingly, few studies used the EPG technique to examine whether the feeding behavior of aphids changes during feeding on mycorrhizal plants.…”
Section: Introductionmentioning
confidence: 99%